Bank Competition and Financial Stability - Berger, Allen N.; Klapper, Leora F.; Turk-Ariss, Rima (World Bank, Washington, DC, 2012)
Under the traditional "competition-fragility" view, more bank competition erodes market power, decreases profit margins, and results in reduced franchise value that encourages bank risk taking. Under the alternative "competition-stability" view, more market power in the loan market may result in greater bank risk as the higher interest rates charged to loan customers make it more difficult to repay loans and exacerbate moral hazard and adverse selection problems. But even if market power in the loan market results in riskier loan portfolios, the overall risks of banks need not increase if banks protect their franchise values by increasing their equity capital or engaging in other risk-mitigating techniques. The authors test these theories by regressing measures of loan risk, bank risk, and bank equity capital on several measures of market power, as well as indicators of the business environment, using data for 8,235 banks in 23 developed nations. The results suggest that - consistent with the traditional "competition-fragility" view - banks with a greater degree of market power also have less overall risk exposure. The data also provide some support for one element of the "competition-stability" view - that market power increases loan portfolio risk. The authors show that this risk may be offset in part by higher equity capital ratios.